Oil, democracy, and development in Africa - Heilbrunn, John R., 1954- (New York, NY : Cambridge University Press, 2014)
"This book focuses on the history, key industry and policy actors, and political economic outcomes in oil-producing African states, filling a gap in the literature on resource-abundant countries by providing an optimistic assessment of circumstances in contemporary Africa. John R. Heilbrunn's historical analysis investigates the origins of how different policy makers responded to inflows of oil windfalls. In doing so, Heilbrunn illustrates how outcomes vary as a consequence of the goals of particular actors that are distinct from the activities in their country's oil sector. This contribution calls for a reassessment of how we consider the impact of oil on developing economies"--
Machine generated contents note: 1. Oil, democracy, and development in Africa; 2. Historic paths: colonialism and its legacies; 3. Oil companies: corporate strategies and profits; 4. Economic growth and phases of production; 5. Resource revenues, corruption, and contracts; 6. Machine politics, oil, and democracy; 7. Conclusion: oil, democracy, and development in Africa.
Includes bibliographical references (pages 231-263) and index.
Keywords: Petroleum industry and trade -- Africa, Sub-Saharan.; Democracy -- Africa, Sub-Saharan.; POLITICAL SCIENCE / Government / General; Africa, Sub-Saharan -- Economic conditions -- 1960-